Profiling hackers: the science of criminal profiling as applied to the world of hacking - Chiesa, Raoul (An Auerbach book, 2009)
Introduction to criminal profiling -- Introducing "cybercrime" -- To be, think and live as a hacker -- The HPP project -- Who are hackers? Part 1 -- Who are hackers? Part 2